The benefits, challenges and impacts of accessing social media group support for breastfeeding: A systematic review - Holly Morse; Amy Brown (Wiley, 2022)
Abstract Breastfeeding support is a key component in meeting the public health responsibility of increasing breastfeeding rates, with access to individualised, convenient and linked support across services central to improved outcomes. With the rise of new technology and the COVID‐19 pandemic, social media (SM) support for breastfeeding has become increasingly popular and it is important to understand how and why mothers access such support, and from whom, to optimise services and to meet mothers' needs. Increasing research is building on women's use and experience of SM for breastfeeding, although there is a paucity of UK data. This systematic review aimed to understand the impacts of SM support for breastfeeding, including benefits and challenges, to establish the evidence for wider provision within maternity services. The search was limited to studies published in English and focused on the self‐directed use of social media groups for breastfeeding (defined as platforms that facilitate group support via interactivity, allowing for user‐generated content and subsequent responses). Of 327 papers retrieved, 13 studies were included for review. The six themes identified were: breastfeeding context, including factors impacting women's decision making; the relational impact of belonging to an online community; increased self‐efficacy; critiques of SM; the nature and types of support commonly sought and received; and breastfeeding duration as an outcome. The findings confirm that mothers value SM groups for community support, which normalises breastfeeding and provides the support they attribute to improved outcomes, and highlight that UK research focused on provision linked to wider services is needed.